2017
DOI: 10.1371/journal.pone.0174302
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community-based complementary food supplement (Yingyangbao) distribution in children aged 6-23 months in poor areas in China

Abstract: BackgroundPoor growth and micronutrient deficiency mainly attack older infants and young children. Some countries have adopted clinically effective measures to combat malnutrition, but the compliance and improvement in efficacy of intervention vehicles in national programs require evaluation.MethodsBaseline and follow-up cross-sectional surveys were conducted before and after a nutrition intervention program in 3 national poverty counties in China. Soybean-based complementary food supplements called Yingyangba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 30 publications
(34 reference statements)
3
28
0
4
Order By: Relevance
“…The possible reason for the low anemia prevalence in this study area may be that the Chinese government has Many studies showed that Yingyangbao intervention and nutrition education could significantly improve the diet quality and nutritional status of children, and good compliance to Yingyangbao contributed to a low risk for childhood anemia [32,33]. In our study, the anemia severity was mainly mild, followed by moderate, which was in agreement with similar studies conducted in Ethiopia [34] and Haiti [35].…”
Section: Anemia Status Of Childrensupporting
confidence: 89%
“…The possible reason for the low anemia prevalence in this study area may be that the Chinese government has Many studies showed that Yingyangbao intervention and nutrition education could significantly improve the diet quality and nutritional status of children, and good compliance to Yingyangbao contributed to a low risk for childhood anemia [32,33]. In our study, the anemia severity was mainly mild, followed by moderate, which was in agreement with similar studies conducted in Ethiopia [34] and Haiti [35].…”
Section: Anemia Status Of Childrensupporting
confidence: 89%
“…Although traditional delivery channels (mainly by village doctors) proved to be effective in our previous study, the key IYCF indicators were still low and the YYB compliance needed to be further improved47 to increase the effectiveness of the interventional programme. In addition, the sustainability of the YYB programme could also be an issue since the anaemia prevalence in Huzhu County went up from 47.8% in 2014 to 59.1% in 2018.…”
Section: Discussionmentioning
confidence: 67%
“…Nutrients supplements have been commonly accepted as effective interventions in reducing child anaemia worldwide 15 46–51. In China, a domestically produced multi-nutrient powders for infants and young children called YYB was developed, and a study conducted in Gansu Province from 2001 to 2004 to test the effectiveness of this complementary food supplement showed that the use of YYB could significantly reduce the anaemia prevalence 48…”
Section: Discussionmentioning
confidence: 99%
“…The finding of this study showed that the overall anemia prevalence among children aged 6-71 months in rural Hunan Province was 9.7%, which was significantly lower than the preschool children in Yingyangbao contributed to a low risk for childhood anemia [28,29].…”
Section: Anemia Status Of Childrenmentioning
confidence: 63%